Syncephalastrum bagoolii (Syncephalastraceae, Mucorales), a new fungus from India - Yadav, Lal Sahab; Patil, Jitendra R; Sharma, Monica; Cordeiro, Thalline Rafhaella Leite; Santiago, André Luiz Cabral Monteiro De Azevedo; Singh, Paras Nath (Phytotaxa, 2025)
During isolation of endophytic fungi from medicinal plants, one isolate of Mucorales appeared as contaminant in culture plates. A few days later, another isolate of Mucorales was found as laboratory contaminant on PDA media. Both isolates were examined morphologically and analyzed phylogenetically using ITS and LSU rDNA. Based on phylogenetic analysis and phenotypic characteristics, both isolates were recognized as a single new species of Syncephalastrum and named as Syncephalastrum bagoolii sp. nov. The latter differs from other species in the genus by forming merosporangiophores variable in length, curved, septate, simple or monopodially or sympodially branched, as well as globose, sub-globose, ovoid, and rarely papillate vesicles. Merosporangia contain up to 4-9 merospores and the basal ones commonly show a denticle attached. In this work the taxonomy and phylogeny of the new species are discussed and a table with morphological characteristics of all Syncephalastrum species is provided.